Evidences of Transesterification, Chain Branching and Cross‐Linking in a Biopolyester Commercial Blend upon Reaction with Dicumyl Peroxide in the Melt. Issue 2 (5th September 2014) - Signori, Francesca; Boggioni, Alessia; Righetti, Maria Cristina; Rondán, Consuelo Escrig; Bronco, Simona; Ciardelli, Francesco
Abstract Aiming at the tuning of thermo‐mechanical features by chemical cross‐linking, a biopolyester commercial blend based on poly(lactic acid) (PLA) with poly(butylene adipate‐co‐terephthalate)(PBAT) (ecovio®T2280, BASF) was processed in Brabender in the presence of dicumyl peroxide (DCP, 0–0.2 wt.‐%). The effect of DCP addition was investigated and rationalized by means of solubility tests and gel content evaluation, as well as rheological, mechanical, and molecular weight analysis of the prepared compounds. Moreover, detailed DSC and TMDSC investigations provided a deep insight into the structural modifications occurred at the macromolecular level. We found that chain branching as well as cross‐linking occurred in the samples processed in the presence of DCP, thus returning compounds having increased toughness and modulated crystalline content and thermal behavior. Noteworthy, the presence of specific, undisclosed additives, triggers the occurrence of peculiar behaviors in the ecovio® commercial blend, not previously observed in model PLA/PBAT blends of similar composition. Despite only partially soluble in chloroform, the new ecovio® DCP‐modified compounds still remained workable in the melt, thus providing a suitable, simple and economically affordable strategy to finely modulate the thermo‐mechanical properties starting from a commercially available, compostable compound.<inline-graphic xlink:href="ark:/27927/pgjf868v8d" content-type="mame201400187-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />